AB1125 Daily Life of Caps Patients Treated with Canakinumab (Ilaris®): Data from the French Observational Study – Envol Study. (9th June 2015) - Kone-Paut, I.; Quartier, P.; Fain, O.; Grateau, G.; Pillet, P.; Despert, V.; Stankovic Stojanovic, K.; Quere, S.; Willemins, L.; Reigneau, O.; Hachulla, E.
Abstract : Background: The long-term efficacy of canakinumab and changes in the daily lives of patients (and their caregivers) have not been thoroughly evaluated since its first use in France in 2007 and its approval for CAPS in 2010. Objectives: A multicentre retrospective, observational study set up to assess the "real life" use of canakinumab in all French CAPS patients ever treated since 2007, to describe their clinical course on a long-term, and to analyse changes in their (and their caregiver's) quality of lives. Methods: We targeted the 70-80 patients ever treated for CAPS in France, at least once and even during a clinical trial. Investigators were known experts in the field of CAPS in France who accepted to take part in the study. Data were collected through questionnaires by phone interviews and medical chart reviews, at treatment initiation, 6 months, 12 months and at the last medical visit. They included: clinical data, canakinumab use in real life conditions, impact on patients' (and caregivers') quality of life, and care consumption. The significance limit was set at 5% for all of the statistical tests. Results: 68 CAPS patients, >90% of the target number, were enrolled (23 children, 45 adults). Sixteen patients (24%) had FCAS, 43 (63%) had MWS and 9 (13%) had NOMID-CINCA. The median duration of treatment was 5 years (from July 2007 to July 2014). >95% of patients remained on treatment. Doses were not modified in nearly half cases (31/68). For 37 patients, dosage adjustments (more often increase) were required (102 in total), especially in younger patients and those with the most severe phenotypes. The global activity of the disease, skin disorders and most of the symptoms were significantly better after canakinumab treatment (p<0.001) at the different study timepoints. The quality of life score also showed a significant improvement as median was 8 before canakinumab versus 2 (p<0.0001). Canakinumab treatment allowed also improvement in patient's daily activities, mood, and social life. Patients reported less school absences (79% versus 36%), and less sick leaves (48% versus 6%) after the initiation of canakinumab. The effect was weaker in CINCA patients; due in part to the late initiation of anti -IL1β treatment. Caregivers (49) were mostly family members and 35% of them had CAPS. They dedicated a mean of 7 hours/week to the CAPS patients before treatment and 4 hours during the last year. They spent on average 11.1 days per year of their job before canakinumab treatment versus 3 days after. The trend was less pronounced for caregivers of NOMID-CINCA patients. Conclusions: ENVOL study showed real-life results similar to those obtained during the phase III clinical trials with canakinumab, reinforcing its sustained activity. The maintenance of more than 95% of patients on therapy confirmed its major benefit to CAPS patients, which was demonstrated herein by the positive impact of canakinumab in patients (and their caregivers) social, emotional, educational and professional lives. Disclosure of Interest: I. Kone-Paut Grant/research support from: SOBI, Novartis, Roche, Consultant for: SOBI, Novartis, Pfizer, Abbvie, Chugai, Speakers bureau: Novartis, SOBI, P. Quartier Grant/research support from: Abbvie, Novartis, Pfizer, Consultant for: Abbvie, Novartis, Servier, SOBI, Speakers bureau: Abbvie, Chugai Roche, Medimmune, Novartis, Sobi, O. Fain Consultant for: Shire et CSL Behring, G. Grateau Grant/research support from: Abbvie, Novartis, Pfizer, Consultant for: Abbvie, Novartis, Servier, SOBI, Speakers bureau: Abbvie, Chugai Roche, Medimmune, Novartis, Sobi, P. Pillet: None declared, V. Despert: None declared, K. STANKOVIC STOJANOVIC: None declared, S. quere Employee of: Novartis employee, L. willemins Employee of: Novartis employee, O. Reigneau Employee of: novartis employee, E. Hachulla Consultant for: Novartis, SOBI